An empirical investigation of German tourist anglers' preferences for angling in Denmark - Ole Bonnichsen; Carsten Lynge Jensen; Søren Bøye Olsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
The quality of angling sites is important for attracting tourists who enjoy recreational angling. In this paper, we conduct an empirical analysis investigating which attributes of angling sites are particularly important for attracting tourist anglers from abroad. We conduct an online survey of 968 German anglers who have recently been abroad on a holiday trip in which they went angling. We focus on the particularly dedicated anglers who state that recreational angling is important for their choice of holiday destination. A stated choice experiment is employed to investigate their preferences for environmental attributes, catch attributes, and social relation/distance attributes of the angling site. We find that preferences are heterogeneous across different angler segments. Three distinct segments of tourist anglers are identified, characterised as "catch oriented" anglers (57 %), "nature oriented" anglers (24 %) and "trophy oriented anglers (19 %)". All three angler segments have the strong preferences for water quality. However, they differ with respect to catch preferences and preferences for social interaction on the angling site. The catch oriented focus on the hunting aspects of angling. A high catch rate as very important for them, but the size of fish is not important. Moreover this segment prefers angling in solitude without disturbance from other anglers. For the "nature oriented" it is very important that the angling takes place in "natural" conditions, the catches rates are not important but they hope to catch large fish, and it is no problem for this group if there are a few other anglers at the angling site. For the "trophy oriented" anglers it is very important to catch large fish, while the catch rate is of moderate importance and they do not mind if there are many anglers at the site. To attract tourist anglers an angling site manager may use this information to target marketing efforts towards segments of tourist that prefer the type and quality of angling characteristics of the angling site in the managers possession. Additionally, he may seek to adjust and improve the angling sites in a way that suits the preferences of specific segments.
Keywords: Q22; Q26; C25; Z32; 330; recreational angling; stated choice experiment; tourism; holiday destination